Development of the Busy Book “Adventures in Protecting Nature” as an Environmental Literacy Innovation for Early Childhood - Nadra Sahi; Yuli Utanto (Universitas Negeri Semarang, 2025)
This study aims to develop the Busy Book “Adventures in Protecting Nature” as a medium for teaching environmental literacy to young children. This product is designed to introduce environmental concepts through various interactive activities that can raise children's awareness of the importance of protecting nature and cleanliness. Using the Research and Development (R&D) method with the 4D model, this study produced media that has been validated by media experts and subject matter experts with very high scores, namely 100% and 81.33%, who assessed this media as very suitable for use. However, there are several suggestions for improvement, such as adding a cardboard coating to increase the durability of the media and adding material related to the impact of environmental pollution. This research contributes to the development of innovative and effective environmental literacy-based learning media, with the aim of increasing children's understanding of environmental issues from an early age.